2018
DOI: 10.1111/ijcp.13272
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of a triple active sore throat lozenge in the treatment of patients with acute pharyngitis: Results of a multi-centre, randomised, placebo-controlled, double-blind, parallel-group trial (DoriPha)

Abstract: ObjectiveThe aim of this multi‐centre, randomised, double‐blind, placebo‐controlled trial was to compare the efficacy and safety of the fixed combination of 0.5 mg tyrothricin, 1.0 mg benzalkonium chloride, and 1.5 mg benzocaine (study drug marketed as Dorithricin®) in repeat dosing for 3 days to match placebo lozenges in the treatment of acute pharyngitis in adults.MethodsPatients (pts, aged ≥18 years) with acute pharyngitis, ie, non‐streptococcal sore throat and moderate‐to‐severe pain (intensity NRS ≥ 7; VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Acute pharyngitis is a common condition encountered in clinical practice, and despite its self-limiting nature, most patients seek painrelieving treatments [1,2]. In this study, the efficacy of the novel ambroxol hard-boiled lozenge formulation was not found to be superior in relieving throat pain compared with placebo.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Acute pharyngitis is a common condition encountered in clinical practice, and despite its self-limiting nature, most patients seek painrelieving treatments [1,2]. In this study, the efficacy of the novel ambroxol hard-boiled lozenge formulation was not found to be superior in relieving throat pain compared with placebo.…”
Section: Discussionmentioning
confidence: 74%
“…Acute pharyngitis is a common condition characterized by inflammation of the upper respiratory tract, with symptoms including sore throat and dysphagia [1]. Although the inflammation usually recedes spontaneously within a few days, the discomfort can be such that most patients seek treatment [2].…”
Section: Introductionmentioning
confidence: 99%
“…[8,9]. It has long been believed that rinsing the mouth with sodium chloride (NaCl) solution can promote healthy gums and fasten oral ulcer healing [10].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical results exhibited significant analgesic effect in throat pain relief. This indicates dothricine could be a better treatment method for management of acute pharyngitis and sore throat [43].…”
Section: Zinc Lozengesmentioning
confidence: 96%